Diagnostic Significance of Mycobacterium tuberculosis T-cell Assays for Active Tuberculosis - Wei-Xia Xuan; Ting-Ting Lu; Zheng Wang; Yun-Xia An; Xiao-Ju Zhang (Chinese Medical Journal, 2017)
Background: Active tuberculosis (TB) with negative results of sputum smear is difficult to be identified. Till now, there is no effective and noninvasive diagnostic method. This study evaluated the diagnostic power of Mycobacterium tuberculosis T-cell (T.SPOT®.TB) assays for active TB. Methods: We retrospectively screened 450 suspected TB patients that were hospitalized in the Respiratory Department of Henan Province People's Hospital from June 2015 to June 2016. The patients were divided into the active, previous, and non-TB groups according to their final diagnosis. We evaluated the diagnostic value of the T-SPOT®.TB assay by constructing receiver operating characteristic (ROC) curves and calculating the optimal diagnostic cutoff value. In addition, we compared the levels of A antigen (ESAT-6) and B antigen (CFP-10) in active TB. Results: The sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative likelihood ratio of T-SPOT®.TB for active TB were 89.78%, 63.16%, 0.56, 0.92, 2.47, and 0.16, respectively. For active TB, the area under the ROC curve (AUC) of the A antigen (0.89) was higher than that of the B antigen (0.86). The AUC of the A antigen for active TB was largest at a cutoff value of 13.5 spot-forming cells (SFCs) per 2.5 × 105 peripheral blood mononuclear cells (PBMCs). The AUC of the A and B antigens was 0.60 and 0.58 for previous TB. The levels of A and B antigen in the active TB group were significantly different from those in the previous- and non-TB groups (A antigen: χ2 = 105.41, P< 0.01 and B antigen: χ2 = 91.03, P< 0.01; A antigen: χ2 = 12.99, P< 0.01 and B antigen: χ2 = 8.56, P< 0.01, respectively). There were no significant differences in the levels of A and B antigens between the non-TB group and previous TB group (A antigen: χ2 = 1.07, P> 0.05 and B antigen: χ2 = 0.77, P> 0.05). Conclusions: T-SPOT®.TB has high sensitivity and specificity for the diagnosis of active TB at a cutoff value of 13.5 SFCs per 2.5 × 105 PBMCs and is not influenced by previous TB.